Spatial Variations of Indoor Air Chemicals in an Apartment Unit and Personal Exposure of Residents - Hironari Sakamoto (MDPI AG, 2021)
Indoor air quality (IAQ) can greatly affect health in people spending much time indoors. However, the influence of IAQ on personal exposure to chemical compounds in Japan remains poorly investigated. Hence, this study aimed to clarify this influence thoroughly within one apartment. We surveyed the concentrations of 61 chemical compounds in the air in nine different spaces within an apartment unit, as well as the personal exposure of two residents in Japan. Using three kinds of diffusive samplers, this study was conducted continuously for 7 days in summer and winter. Health risks were evaluated by calculating the margin of exposure (MOE) using the measured concentrations. Some chemical concentrations showed large spatial variations and the personal exposure concentrations of these compounds also differed among residents. According to the calculated MOE, the chemicals with the highest health risk were acrolein, p-dichlorobenzene, and acetaldehyde in summer and acrolein, nitrogen dioxide, formic acid, p-dichlorobenzene, and benzene in winter. The IAQ of the house could be divided in two, and the IAQ in the space where residents spent much time (i.e., bedroom) highly affected each of the residents’ exposure. Investigating chemical concentrations in multiple spaces (including bedroom and living room) is necessary to understand the effect of IAQ on personal exposure.